Ensaios de uma metodologia da experiência crítico-afetiva nas aulas de educação física: impactos sobre as relações de gênero e o empoderamento das meninas - Pereira, Ana Cristina Gabriel (2020)
The proposal of the present study originated from the possibilities of developing sensibility and consideration, amongst the students of a municipal public school, about gender inequalities, as well as the empowerment of girls in sports practices. Starting with this premise, we formulated an educational proposal guided by an intervention model that we denominated Critical-Affective Experience Methodology (“CAEM”). The goal of the study was to analyze the co-educational processes emerging from an intervention applying the CAEM in Physical Education classes provided to 6th grade (elementary school) students. This active research was guided by the implementation of an educational unit composed by seventeen classes based on the co-education and knowledge of the internal and external logics of Invasion Sport Games (“ISG”). The instruments for data production included Class Journals, Individual Narratives and small conversation groups, and the observation and analysis of the video recording of the ISG, which were obtained through footage and audio recording. Based on the data collected, their results and analysis are presented concurrently and in a fluid manner through two general categories. In the first category, “Gender relations in the co-educational context of the Invasion Sport Games”, issues surrounding the male domination in ISG and in the society and the production of gender differences and inequalities were highlighted. In the second category, “Impacts of the Critical-Affective Experience Methodology”, the subcategories that emerged denote processes for the girls’ empowerment through oral expression, processes for tactical and technical empowerment, and co-educational processes for overcoming sexism. We believe that the Critical-Affective Experience Methodology enabled the emergence of co-educational processes, such as the awareness about the power hierarchy in the gender relations, a confrontational posture from the girls before the social injustices, more balanced and democratic access to ISG amongst boys and girls, effective participation of the female students in the ISG, and the improvement in the interaction amongst boys and girls in (and beyond) the Physical Education classes.